Shared decision making in patients with low risk chest pain: prospective randomized pragmatic trial. (5th December 2016) - Hess, Erik P; Hollander, Judd E; Schaffer, Jason T; Kline, Jeffrey A; Torres, Carlos A; Diercks, Deborah B; Jones, Russell; Owen, Kelly P; Meisel, Zachary F; Demers, Michel; Leblanc, Annie; Shah, Nilay D; et al.
Abstract : Objective To compare the effectiveness of shared decision making with usual care in choice of admission for observation and further cardiac testing or for referral for outpatient evaluation in patients with possible acute coronary syndrome. Design Multicenter pragmatic parallel randomized controlled trial. Setting Six emergency departments in the United States. Participants 898 adults (aged >17 years) with a primary complaint of chest pain who were being considered for admission to an observation unit for cardiac testing (451 were allocated to the decision aid and 447 to usual care), and 361 emergency clinicians (emergency physicians, nurse practitioners, and physician assistants) caring for patients with chest pain. Interventions Patients were randomly assigned (1:1) by an electronic, web based system to shared decision making facilitated by a decision aid or to usual care. The primary outcome, selected by patient and caregiver advisers, was patient knowledge of their risk for acute coronary syndrome and options for care; secondary outcomes were involvement in the decision to be admitted, proportion of patients admitted for cardiac testing, and the 30 day rate of major adverse cardiac events. Results Compared with the usual care arm, patients in the decision aid arm had greater knowledge of their risk for acute coronary syndrome and options for care (questions correct: decision aid, 4.2 v usual care, 3.6; mean difference 0.66, 95% confidence interval 0.46 to 0.86), were more involved in the decision (observing patient involvement scores: decision aid, 18.3 v usual care, 7.9; 10.3, 9.1 to 11.5), and less frequently decided with their clinician to be admitted for cardiac testing (decision aid, 37% v usual care, 52%; absolute difference 15%; P<0.001). There were no major adverse cardiac events due to the intervention. Conclusions Use of a decision aid in patients at low risk for acute coronary syndrome increased patient knowledge about their risk, increased engagement, and safely decreased the rate of admission to an observation unit for cardiac testing. Trial registration ClinicalTrials.gov NCT01969240 .